2020
DOI: 10.1051/e3sconf/202017216004
|View full text |Cite
|
Sign up to set email alerts
|

Optimum envelope design toward zero energy buildings in Iran

Abstract: Buildings, commercial and residential combined, account for around 40% of total energy consumption in Iran. Energy consumption in buildings is predicted to increase in the the coming decades decades and immediate actions are required to meet the needs of future generations. Zero energy building (ZEB) is an important concept that can help nations to have a sustainable future. An important step for building a ZEB is to minimize the energy lost from the building, and the envelope of buildings plays a vital role i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 13 publications
(30 reference statements)
0
7
0
Order By: Relevance
“…The CC PC has been calculated on the basis of the Iranian market reference for the proposed interventions [7,75,76]. In addition, because of the lack of a standardized and detailed price list for construction materials, the authors evaluated and actualized the prices by comparing the references [7,75,76] with the current Iranian market in IRR, then converted to USD considering an IRR/USD exchange rate of ~1/0.000024 [77].…”
Section: Energy Environmental and Economic Methodologiesmentioning
confidence: 99%
See 2 more Smart Citations
“…The CC PC has been calculated on the basis of the Iranian market reference for the proposed interventions [7,75,76]. In addition, because of the lack of a standardized and detailed price list for construction materials, the authors evaluated and actualized the prices by comparing the references [7,75,76] with the current Iranian market in IRR, then converted to USD considering an IRR/USD exchange rate of ~1/0.000024 [77].…”
Section: Energy Environmental and Economic Methodologiesmentioning
confidence: 99%
“…The CC PC has been calculated on the basis of the Iranian market reference for the proposed interventions [7,75,76]. In addition, because of the lack of a standardized and detailed price list for construction materials, the authors evaluated and actualized the prices by comparing the references [7,75,76] with the current Iranian market in IRR, then converted to USD considering an IRR/USD exchange rate of ~1/0.000024 [77]. Therefore, in this work, the cost of the whole SS facade system, including the renovation materials (for the insulation panels, metal structure for the ventilated facade, and tensile material), and the cost for the scaffolding and the cost of labor, has been assumed equal to 21.78 $/m 2 .…”
Section: Energy Environmental and Economic Methodologiesmentioning
confidence: 99%
See 1 more Smart Citation
“…For identifying suitable industrial zones, effective factors should be identified first. In this study, the factors were selected from previous similar research [1,2,3,20,21,22,23,24,25,26,27], and national and international regulations. A comprehensive set of factors were identified and then the factors were carefully screened to select the final factors based on data availability.…”
Section: B Data Collection and Preparation Of Layersmentioning
confidence: 99%
“…In most regions, building energy standards are established but contain limited information on building envelope components. Usually, those standards provide the allowable thermal resistance or transmittance of the envelope components and WWR in some cases [39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55]. The comprehensive design approach involves building performance simulations, which are time-consuming and require knowledge of complicated processes.…”
Section: Introductionmentioning
confidence: 99%